Agile Management in the Scalability of Software Startups: The Role of Organizational Culture - Najafgholizadeh, Amin; Seyfollahzadeh Sarai, Tohid (Future of Work and Digital Management Journal, 2026)
Software startups undergoing scalability face multiple cultural and structural challenges that can influence the effective implementation of agile approaches. This study aims to elucidate the interaction between organizational culture and agile management in these organizations, with a focus on the role of cultural factors in the success or failure of Agile. The present research was conducted using a qualitative and exploratory approach based on grounded theory. Data were collected through 16 semi-structured interviews with managers, founders, and Agile coaches in software startups, and data analysis was carried out through open, axial, and selective coding until theoretical saturation was reached. The findings indicated that concepts such as transparency, continuous learning, trust, self-organization, and team coordination emerge as facilitators of successful Agile implementation, whereas hierarchical control, resistance to change, and short-term pressures represent key obstacles in the path toward agile scalability. The analysis of the relationships among these categories led to the development of a paradigmatic model in which transparency and continuous learning play a causal role in strengthening agile performance, while control structures and time pressure act as inhibiting conditions. The results of the study indicate that the success of scaling Agile depends less on formal frameworks and more on the quality of organizational culture and the learning capacity of teams. Accordingly, enhancing transparency, documenting experiences, strengthening team trust, and reducing hierarchical barriers are among the most important actions that managers should consider to support agile transformation.